Mucin expression in pleomorphic adenoma of salivary gland: a potential role for MUC1 as a marker to predict recurrence. Issue 8 (27th July 2004) - Hamada, T; Matsukita, S; Goto, M; Kitajima, S; Batra, S K; Irimura, T; Sueyoshi, K; Sugihara, K; Yonezawa, S
Abstract : Background: Pleomorphic adenoma of the salivary gland (PA) is essentially a benign neoplasm. However, patients with recurrent PA are difficult to manage. There are rare reports on useful immunohistochemical markers to detect a high risk of recurrence when the primary lesions are resected. Aims: To find a new marker to predict the recurrence of PA. Methods: Primary lesions of PA were collected from nine patients showing subsequent recurrence and from 40 patients without recurrence during at least 10 years of follow up of the disease. Paraffin wax embedded tumour samples of the two groups were examined for the expression profiles of MUC1 (differentially glycosylated forms), MUC2, MUC4, MUC5AC, and MUC6 using immunohistochemistry. Several clinicopathological factors were also examined. Results: In univariate analysis of the factors examined, MUC1/DF3 high expression (more than 30% of the neoplastic cells stained) in the primary lesions was seen more frequently in patients with recurrence (four of nine) than in those without recurrence (three of 40; p = 0.011). Larger tumour size (more than 3.0 cm) of the primary PA was also a significant (p = 0.035) risk factor for the recurrence of PA. In multivariate analysis, only high expression of MUC1/DF3 was found to be a significant independent risk factor for the recurrence of PA (p = 0.021). Conclusions: Expression of MUC1/DF3 in PA is a useful marker to predict its recurrence. Those patients with PA showing positive MUC1/DF3 expression should be followed up carefully.